An evaluation of fevipiprant for the treatment of asthma: a promising new therapy?. (12th December 2018) - Murillo, Juan Carlos; Dimov, Ves; Gonzalez-Estrada, Alexei
ABSTRACT: Introduction: Asthma is a heterogeneous disease characterized by chronic airway inflammation that affects more than 230 million people worldwide. Current guidelines recommend an escalating stepwise decision model for the management of asthma. However, disease control continues to be a challenge, particularly in patients with severe asthma. Biologics have proven to be an effective add-on treatment especially in eosinophilic or type 2 airway disease. Comparatively, pre-biologics may represent a successful novel therapy. Fevipiprant (QAW039) is a selective, reversible, antagonist of the prostaglandin D2 receptor (DP2 ). Areas covered: The authors review the mechanism of action of fevipiprant as well as its pharmacokinetics, pharmacodynamics, tolerability, efficacy, and safety. Comparative therapies are also described. A comprehensive literature review was performed using: the PubMed central database, U.S. National Institutes of Health's National Library of Medicine database (NIH/NLM) and the NLM clinical trials database. Expert opinion: Fevipipiprant is a promising prebiologic therapy with convenient dosing, oral administration, and an acceptable safety profile. However, the spectrum of asthmatic patients that may benefit from this therapy is somehow limited to (i.e. moderate to severe eosinophilic asthma). Results from phase III clinical trials are needed to assess whether fevipiprant would lead to a reduction in exacerbation rates and perhaps broaden the target population.